Comparative study between effects of single and dual chamber pacemaker on stroke volume, cardiac output and strain using 3D echocardiography, pulsed Doppler method and global longitudinal strain (GLS). (25th November 2020) - Dawood, M; Elsharkawy, E; Abdel-Hay, M.A; Nawar, M
Abstract: Background: Dual-chamber cardiac pacing is thought to deliver higher clinical benefits as compared with single-chamber ventricular pacing. During the last two decades, 3D-echocardiography developed from a sophisticated, time-consuming method preferably used as a scientific tool towards a routine clinical approach. At present, available evidence suggested that 3D echocardiography provided improved accuracy and reproducibility over 2D methods for LV volume and function calculation. It was also more useful for early detection of volumetric changes associated with changes in cardiac hemodynamics. Methods: This was an observational study of fifty consecutive patients without structural heart disease and preserved ejection fraction (EF>50%) presented with high grade atrioventricular block for permanent pacemaker implantation. They were assigned to receive a single-chamber ventricular pacemaker (23patients) or a dual-chamber pacemaker (27 patients). Stroke volume and cardiac output was assessed by full volume 3D echo and pulsed wave Doppler before implantation, at one-week and 6-months after implantation. For the Doppler method, LVOT diameter was measured for each patient at baseline and same value was used at follow up to avoid any confounding factors. GLS was measured at all visits. Results: At one-week post pacing, both groups showed a significant decrease in SV due to a drop in EDV while ESV did not change significantly. There was a significant increase in cardiac output (COP) more in dual-chamber pacing group than in the group with single-chamber pacing. However, there were no significant differences between both groups regarding stroke volume (SV), end-systolic volume (ESV), end-diastolic volume (EDV) or ejection fraction (EF) during all time intervals (pre-pacing, at one-week and 6-months post pacing). GLS showed equal decrease in both groups. At 6 months, SV continued to decrease, and COP showed significant decrease. This drop in SV and COP was due to a significant increase in ESV while EDV did not show significant change at 6-month follow up. There was no significant difference between full volume 3D and Doppler methods regarding SV and COP values at all time intervals in both groups. GLS showed additional equal decrease in both groups. Conclusion: Dual chamber pacing provided higher COP than single chamber pacing. This is due to pacing at higher heart rates, not due to increase in SV by maintaining atrioventricular synchrony. It was shown in both experimental and clinical studies that RV pacing leads to ventricular dyssynchrony, similar to that of left bundle branch block with subsequent electrical, mechanical and anatomical changes leading to detrimental effects on left ventricular structure and function. Both groups showed significant drop in GLS plus SV, COP and EF at 6-months due to significant increase in ESV. 2D echocardiography and Doppler method were not inferior to 3D echocardiography regarding calculation of SV and COP. Funding Acknowledgement: Type of funding source: None